Trigonocephaly and associated minor anomalies in mother and son. - Hunter, A G (1976)
A mother and her son are described with neonatal trigonocephaly, multiple suture synostosis; shallow orbits; unusual nose; deviation of the terminal phalanges of fingers 1, 2, and 5; and broad toes which radiologically may show duplication of the terminal phalanx. Untreated, the condition leads to a disfiguring oxycephaly with hypotelorism. This appears to be the first documented instance of autosomal dominant trigonocephaly. The importance of the minor anomalies in its recognition and its good prognosis are emphasized.